EFEKTIFITAS PERENCANAAN PEMBANGUNAN DAERAH DI KALIMANTAN - PKP2A III LAN Samarinda, Tim Kajian (Jurnal Borneo Administrator, 2010)
The success of local government in carrying out the development will be seen from the extent of changes that occur after regional development programs and activities are implemented. Nevertheless, a good development is also preceded by a good planning process. It is because development is series that began through the long process of planning, implementation, monitoring and evaluation. Regional development planning can be seen from 2 (two) aspects: the process of preparation of development plans and aspects of the content development plan to be implemented.  Keywords: development planning, effectiveness